PERLINDUNGAN HAK CIPTA TERHADAP LAGU YANG DI ARANSEMEN ULANG DI YOUTUBE BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - NIM. A1011191161, MIKHAL ABIGAEL (Fakultas Hukum Universitas Tanjungpura, 2023)
ABSTRACT The global technological advancements have enabled society to enjoy entertainment through electronic media like YouTube, which has both positive aspects in terms of easier access to music and negative consequences due to the misuse of technology, such as the uploading of songs without the creator's permission. This research aims to investigate the legal protection provided to songwriters when their work is uploaded on YouTube by others. Additionally, it explores the efforts that copyright holders can take and the legal consequences faced by video creators on YouTube who upload content without permission. The research methodology employed is normative legal research, with data collected from legal literature. Based on Article 9 of Law Number 28 of 2014 regarding Copyright, songwriters receive legal protection for their work uploaded on YouTube for economic purposes, regardless of the medium used. YouTube also provides protection by removing videos that infringe copyright after receiving notifications. Songwriters can take preventive measures by registering their copyright to claim royalties through links provided by the Ministry of Law and Human Rights, which is now easily accessible online. Keywords : Copyright, Youtube, Rearrangement, License, Royalty ABSTRAK Perkembangan teknologi global memungkinkan masyarakat menikmati hiburan melalui media elektronik seperti Youtube, yang memiliki dampak positif dalam hal akses musik, namun juga dampak negatif dengan penyalahgunaan teknologi, yaitu unggahan video lagu tanpa izin pencipta. Penelitian ini bertujuan menginvestigasi perlindungan hukum bagi pencipta lagu ketika karya mereka diunggah di Youtube oleh pihak lain, serta upaya yang dapat dilakukan pemegang hak cipta dan konsekuensi hukum bagi pembuat video yang melanggar hak cipta di Youtube. Metode yang digunakan adalah penelitian hukum normatif dengan data dari literatur hukum. Berdasarkan Pasal 9 Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta, pencipta lagu mendapatkan perlindungan hukum terkait karyanya yang diunggah di Youtube untuk kepentingan ekonomi, tanpa tergantung pada media yang digunakan. Youtube juga memberikan perlindungan dengan menghapus video yang melanggar hak cipta setelah pemberitahuan. Pencipta dapat melakukan pendaftaran hak cipta untuk mengklaim royalti melalui link yang disediakan oleh Kementerian Hukum dan HAM secara online. Kata Kunci : Hak Cipta, Youtube, Aransemen Ulang, Lisensi, Royalti